Literature Review on the Elasticity of Regional Original Revenue (PAD) to Gross Regional Domestic Product (GRDP) - Dhea Ayu Safira; Abdul Manan; Eka Agustiani (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This study aims to analyze the growth of Local Original Income (PAD) to Gross Regional Domestic Product (GRDP) and analyze the Elasticity of Local Original Income (PAD) to Gross Regional Domestic Product (GRDP) in Central Lombok Regency in 2014-2023. The research approach uses quantitative descriptive. The data analysis technique used is Growth Analysis, Contribution and Elasticity criteria according to the criteria based on applicable provisions. The results of the study show that the growth of PAD in Central Lombok Regency during the 2014-2023 period was 11.52%, while the average growth of GRDP during the 2014-2023 period was 3.78%. Which means that when compared to the average of both, the contribution of PAD to GRDP in Central Lombok Regency in 2014-2024 is included in the very low criteria. The elasticity of PAD to GRDP in Central Lombok Regency during the 2014-2023 period averaged 0.13, including in the Inelastic category. This means that even though PAD increases, its impact on GRDP is relatively small.